Community Based Management for Flood Disaster: A Case Study of Khon Kaen Province and Songkhla Province - Prapasavat , Kobkarn; Laohavichien, Uthai (Journal of Management Science Nakhon Pathom Rajabhat University, 2023)
This research aims to 1) Study the community-based flood disaster management approach: case studies in Khon Kaen and Songkhla provinces. 2) To study the nature of community participation and level in community-based flood disaster management, a case study in Khon Kaen and Songkhla provinces. 3) To study the problems of community-based flood disaster management, case studies in Khon Kaen and Songkhla provinces. 4) Propose guidelines for community-based disaster management a case study of Khon Kaen and Songkhla provinces. The research methodology used a qualitative case study approach, with in-depth interviews of 30 key informants 15 per province from regional organizations, local government organizations, and communities involved in disaster management based on community involvement. In addition, document analysis and non - participant observation were used, and data were analyzed using inductive analysis and cross-case analysis. The study found that 1) community-based disaster management was the foundation of both case studies, which involved dividing the disaster management process into three stages: before, during, and after the event. This was done in the form of a committee and working group appointed by the provincial governor, in compliance with the Disaster Prevention and Mitigation Act of 2007. 2) The nature of community participation involved community surveillance, participation in meetings, expression of opinions, and the establishment of community volunteers. The level of community participation in both cases was only nominal. 3) Regarding the problem of community-based disaster management in both cases, the study found that there was a problem with insufficient budget allocation for disaster management, even though there had been joint planning among various sectors. 4) Recommendations included the need for government agencies to genuinely involve the community in disaster management, and the need to amend laws to promote participation at all levels, in order to reduce risk for the community. It is also important to enhance the knowledge, capabilities of both government agencies, communities in disaster management, to maximize the benefits and efficiency of community capabilities. From the cross-synthesis of the two community-based flood disaster management case studies, it was found that the disaster management approaches were similar. Things that are different. Songkhla has a plan at the community level for each community, with all sectors participating in planning and providing disaster knowledge to the community. A flood map is prepared. Create a map of vulnerable groups and the preparation of a nanny house or head of the alleys In doing this kind of operation, the province of Khon Kaen does not operate. And different contributions by Khon Kaen Province Participation was at level 4, consultation level, and Songkhla was at level 5, which was just a consolation. Article history: Received 2 May 2023 Revised 7 June 2023 Accepted 9 June 2023 SIMILARITY INDEX = 3.02%